2016
DOI: 10.1073/pnas.1610081113
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell dynamics and variability of MAPK activity in a yeast differentiation pathway

Abstract: In response to pheromones, yeast cells activate a MAPK pathway to direct processes important for mating, including gene induction, cellcycle arrest, and polarized cell growth. Although a variety of assays have been able to elucidate signaling activities at multiple steps in the pathway, measurements of MAPK activity during the pheromone response have remained elusive, and our understanding of single-cell signaling behavior is incomplete. Using a yeast-optimized FRET-based mammalian Erk-activity reporter to mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 65 publications
9
61
0
Order By: Relevance
“…If both partners are able to arrest in G1, they will extend a mating projection toward each other and polarize their sensing and secretory machinery. This will lead to a local increase in pheromone concentration that will be associated with an increase in signal transduction (Appendix Fig S20; Conlon et al , ). Mating experiments performed with a mutant unable to degrade pheromone ( bar1∆ ) clearly demonstrate that p FIG1 induction is triggered by the concentration of pheromone sensed by the cells and not by cell–cell contacts.…”
Section: Discussionmentioning
confidence: 99%
“…If both partners are able to arrest in G1, they will extend a mating projection toward each other and polarize their sensing and secretory machinery. This will lead to a local increase in pheromone concentration that will be associated with an increase in signal transduction (Appendix Fig S20; Conlon et al , ). Mating experiments performed with a mutant unable to degrade pheromone ( bar1∆ ) clearly demonstrate that p FIG1 induction is triggered by the concentration of pheromone sensed by the cells and not by cell–cell contacts.…”
Section: Discussionmentioning
confidence: 99%
“…The SKARS strategy provides a global measurement of kinase activity in a cell, while FRET biosensors can monitor local changes in kinase activity 54,55 . For some studies, FRET biosensors might therefore have a clear advantage by adding a spatial information for signaling activity.…”
Section: Resultsmentioning
confidence: 99%
“…The first was the realization that Fus3, but not Kss1, is responsible for gradient tracking (Conlon, Gelin-Licht, Ganesan, Zhang, & Levchenko, 2016;Erdman & Snyder, 2001;Errede, Vered, Ford, Pena, & Elston, 2015;Hao et al, 2008;Hegemann et al, 2015; although another group reported a specific requirement for Kss1; Paliwal et al, 2007). This was surprising to us given that Fus3 and Kss1 are both activated by the same upstream protein kinases, and either MAPK can sustain mating transcription and elongated growth (Breitkreutz et al, 2001;Conlon et al, 2016;Erdman & Snyder, 2001;Errede et al, 2015;Hao et al, 2008;Hegemann et al, 2015;Paliwal et al, 2007;Roberts et al, 2000;Zeitlinger et al, 2003). In parallel experiments using phospho-p44/ p42 antibodies, we determined that gradient tracking is the result of the distinct temporal and dose-dependent activation properties of Fus3.…”
Section: Discussionmentioning
confidence: 99%